Fracture load and survival of anatomically representative monolithic lithium disilicate crowns with reduced tooth preparation and ceramic thickness - Nawafleh, Noor A (J Adv Prosthodont, 2017)
PURPOSE: To investigate the effect of reducing tooth preparation and ceramic thickness on fracture resistance of lithium disilicate crowns. MATERIALS AND METHODS: Specimen preparation included a standard complete crown preparation of a typodont mandibular left first molar with an occlusal reduction of 2 mm, proximal/axial wall reduction of 1.5 mm, and 1.0 mm deep chamfer (Group A). Another typodont mandibular first molar was prepared with less tooth reduction: 1 mm occlusal and proximal/axial wall reduction and 0.8 mm chamfer (Group B). Twenty crowns were milled from each preparation corresponding to control group (n=5) and conditioned group of simultaneous thermal and mechanical loading in aqueous environment (n=15). All crowns were then loaded until fracture to determine the fracture load. RESULTS: The mean (SD) fracture load values (in Newton) for Group A were 2340 (83) and 2149 (649), and for Group B, 1752 (134) and 1054 (249) without and with fatigue, respectively. Reducing tooth preparation thickness significantly decreased fracture load of the crowns at baseline and after fatigue application. After fatigue, the mean fracture load statistically significantly decreased (P<.001) in Group B; however, it was not affected (P>.05) in Group A. CONCLUSION: Reducing the amount of tooth preparation by 0.5 mm on the occlusal and proximal/axial wall with a 0.8 mm chamfer significantly reduced fracture load of the restoration. Tooth reduction required for lithium disilicate crowns is a crucial factor for a long-term successful application of this all-ceramic system.